ANALYSIS OF THE APPLICATION OF MALCOLM BALDRIGE CRITERIA (MBCFPE) TO BUSINESS ACTORS IN INDONESIA - Vira Aulia Gusfi; Ulul Azmi; Prie Dewi Listanti; Kusuma Chandra Kirana (ZILLZELL MEDIA PRIMA, 2024)
This research explores the challenges and opportunities for Micro, Small and Medium Enterprises (MSMEs) in Indonesia, focusing on the implementation of the Malcolm Baldrige Criteria for Performance Excellence. Although the MSME sector in Indonesia is very large, limited capital, access to technology, and market reach hinder their competitiveness against larger companies. Along with that, the proliferation of online media adds complexity to the business landscape, demanding rapid adaptation. Strategic human resource management is emerging as a critical factor for long-term organizational development. The research uses the Malcolm Baldrige Award as a benchmark for performance appraisal, which includes leadership, strategic planning, customer focus, measurement and analysis, workforce focus, process management, and results. The study sampled six businesses, revealing the varying impact of these criteria on their performance. Key findings highlight the key role of leadership and customer-focus in influencing MSME outcomes, while other criteria show mixed and sometimes less significant effects. Full implementation challenges include a lack of a clear vision-mission statement, lack of organizational structure, and limited emphasis on product innovation. The research concludes with recommendations for MSMEs in Indonesia, emphasizing the importance of developing a clear vision, improving organizational structure, and increasing focus on innovation. These findings provide deep insight into the dynamics of MSMEs and offer strategic direction to navigate Indonesia's evolving business landscape.